The Effect of Financial Technology (Fintech) and Service Providers on Customer Value: Case Study on Gas Station Services in Surabaya City - Purwonegoro, Stefiany Agung; Fatihudin, Didin; Mockhlas, Mochamad; Mahardhika, Budi Wahyu (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
This study aims to analyze the effect of financial technology and service providers on customer value in Surabaya City. The variables tested in this study include financial technology (X₁), service providers (X₂), and customer value (Y) as the dependent variable. The sample used in this study amounted to 87 respondents who are users of gas stations in Surabaya, with three types of fuel service providers, namely Pertamina, SHELL, and British Petroleum (BP). Sampling was done purposively by selecting respondents who actively use the gas station service. Hypothesis testing was conducted using multiple linear regression to analyze the effect of financial technology and service providers on customer value. Hypothesis testing results show that financial technology significantly influences customer value, with a significance value of 0.001, smaller than 0.05. On the other hand, service providers also influence customer value, albeit with a significance value of 0.099, which is insignificant at the 5% significance level. Based on these results, financial technology contributes more to perceived customer value than service providers. These findings indicate the importance of innovation in Fintech as a key factor in improving customer satisfaction in the gas station service sector.